2007
DOI: 10.3748/wjg.v13.i10.1612
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular analysis of hereditary non-polyposis colorectal cancer in Chinese colorectal cancer patients

Abstract: The frequency of HNPCC is approximately 10% among all Chinese CRC cases. The MSI and IHC detections for hMSH2/hMLH1 proteins are reliable pre-screening tests for hMLH1/hMSH2 germline mutations in families suspected of having HNPCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Chinese LS screening criteria decreased the pedigree LS numbers and are more suitable for small Chinese pedigrees (Genetics Group of the Committee of Colorectal Cancer, China Anti-cancer Association, 2018). Wang et al (2007) have reported that the sensitivity and specificity of immunohistochemistry for predicting mutations to screen hereditary nonpolyposis colorectal cancer (HNPCC) in Chinese CRC cases suspected of HNPCC were 79% and 77%, respectively. Due to the cost of the test, only some of the dMLH1 or dPMS2 patients accepted advanced detection to excluding BRAF V600E mutation or MLH1 promoter hypermethylation and only 25 cases accepted NGS for LS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chinese LS screening criteria decreased the pedigree LS numbers and are more suitable for small Chinese pedigrees (Genetics Group of the Committee of Colorectal Cancer, China Anti-cancer Association, 2018). Wang et al (2007) have reported that the sensitivity and specificity of immunohistochemistry for predicting mutations to screen hereditary nonpolyposis colorectal cancer (HNPCC) in Chinese CRC cases suspected of HNPCC were 79% and 77%, respectively. Due to the cost of the test, only some of the dMLH1 or dPMS2 patients accepted advanced detection to excluding BRAF V600E mutation or MLH1 promoter hypermethylation and only 25 cases accepted NGS for LS.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry testing for MMR state is the primary step for LS screening universally which is cost-effective and easily available (Wong et al ., 2018; Gudgeon et al ., 2019; Sarode and Robinson 2019). The sensitivity of immunohistochemistry testing for MMR was over 90% (Wang et al ., 2007; Shia, 2008). Increasingly studies have demonstrated that the predictive value of immunohistochemistry is as sensitive as MSI testing.…”
Section: Introductionmentioning
confidence: 99%
“…Fishel et al and Leach et al first independently reported the mutation of MMR genes is associated with Lynch syndrome according to their study that showed the mutation of MSH2 gene causes Lynch syndrome [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Figure 3.The function of DNA mismatch repair genes and its correlations with the human disease is very significant. Germline mutations in the human homologue of the bacteria mutS gene (MSH2) predispose individuals to Lynch syndrome Wang et al[14]; Pérez-Cabornero et al[15]. DNA mismatch repair (MMR) genes are following a highly conserved biological pathway playing a significant role in maintaining genomic stability.…”
mentioning
confidence: 99%